Hubungan Stigma Afiliasi dan Kualitas Hidup Pengasuh Anak Gangguan Spektrum Autisme - Masyithah, Izza Ulya; Bisri, Moh. (Flourishing Journal, 2024)
Autism spectrum disorder is a neurological and developmental disorder that affects an individual's ability to behave and perform social interaction, learning and communication. Autism spectrum disorder cases not only affect the individual but also affect family life. The quality of life of caregivers of children with autism spectrum disorders is not only faced with the level of the child's autism disorder but also the negative social attitudes of society, which in this case is affiliate stigma. This study aims to determine the relationship between affiliate stigma and the quality of life of caregivers of children with autism spectrum disorders. The research method used is a quantitative method with a correlational research design. The population of this research is the community of caregivers of autistic children in Malang City with 42 community members participating. The results of this study found that there was a significant relationship between affiliate stigma and the quality of life of caregivers of children with autism spectrum disorders and it was negatively correlated a coefficient of -0.536. This shows that the lower the level of stigmatization of belonging, the higher the level of quality of life. AbstrakGangguan spektrum autisme merupakan gangguan neurologis dan perkembangan yang mempengaruhi kemampuan individu untuk berperilaku serta melakukan interaksi sosial, belajar dan komunikasi. Kasus gangguan spektrum autism tidak hanya mempengaruhi individu melainkan juga mempengaruhi kehidupan keluarga. Kualitas hidup pengasuh anak dengan gangguan spektrum autism tidak hanya dipengaruhi oleh tingkat gangguan autisme anak, tetapi juga sikap sosial negatif masyarakat yang dalam hal ini adalah stigma afiliasi. Penelitian ini bertujuan untuk mengetahui hubungan antara stigma afiliasi dan kualitas hidup pengasuh anak gangguan spektrum autisme. Metode penelitian yang digunakan adalah metode kuantitatif dengan desain penelitian korelasional. Populasi penelitian ini yakni komunitas para pengasuh anak autis di Kota Malang dengan jumlah responden yang berpartisipasi sebanyak 42 anggota komunitas. Hasil penelitian ini ditemukan terdapat hubungan yang signifikan antara stigma afiliasi dan kualitas hidup pengasuh anak gangguan spektrum autisme serta berkorelasi secara negatif dengan koefisien -0,536. Hal ini menunjukkan semakin rendah tingkat stigma afiliasi maka akan semakin tinggi tingkat kualitas hidup.